Risk Factor Report on Informal Waste Recovery Workers from San Cristóbal Locality – Bogotá - Gregorio Enrique PUELLO-SOCARRÁS; Ana Emelis OBREGÓN FLÓREZ; Ana Carolina SERNA RUBIO; Diana Marcela BALLÉN BUITRAGO (Communications of International Proceedings, 2021)
A social innovation project was made for the effective communication of labor risk factors that informal recyclers face everyday in San Cristóbal Sur locality in the city of Bogotá (Colombia). In this report, a diagnosis of a group of approximately 100 informal recyclers and their working conditions was made. For this matter, a non-probabilistic snowball sample was carried out. The data gathering instrument used was built taking into account the workstation planned inspections NTC4114 standard criteria. Alongside this, a social mapping strategy was carried out to establish the most frequent workplace accidents and occupational diseases associated with recycling activities. Later on, a risks and dangers matrix based on the GTC45standard layout, setting up the scheme for social innovation processes focused on knowledge transmission among different communities. The project allowed the establishment of communication initiative parameters for network enhancement between educational communities and the ex officio recuperators, thus stimulating and promoting knowledge sharing regarding waste disposal good practices in domestic scenarios. These networks, later on, allowed the generation of an action-driven strategy focused on accountability at the end of the consumer chains, especially for the resulting negative impact of waste disposal mispractices on the informal recycling activity. It is expected that these social and environmental research projects stimulate behavioral changes in all those involved in waste management and consumer chains, thus mitigating risks on waste disposal for recyclers.
Keywords: Social Innovation; Social knowledge apprehension; Occupational Risks; Informal Labor